2015
DOI: 10.3831/kpi.2015.18.027
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Regulates Mitochondrial Function During 7,12-Dimethyl Benz[a]anthracene Induced Experimental Mammary Carcinogenesis

Abstract: Objectives:The present study was undertaken to determine the modulatory effect of taurine on the liver mitochondrial enzyme system with reference to mitochondrial lipid peroxidation (LPO), antioxidants, major tricarboxylic acid cycle enzymes, and electron transport chain enzymes during 7,12-dimethyl benz[a]anthracene (DMBA) induced breast cancer in Sprague-Dawley rats.Methods:Animals in which breast cancer had been induced by using DMBA (25 mg/kg body weight) showed an increase in mitochondrial LPO together wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Recent studies have found that it has good anti-tumor effects [914]. For example, Tau can inhibit the in vitro invasion and migration of breast cancer cells and has a better therapeutic effect against methylbenzanthracene (DMBA)-induced breast cancer [11,12]. Our previous studies have shown that Tau can inhibit the apoptosis of cardiomyocytes subjected to ischemia/reperfusion [15] and can induce (or promote) apoptosis in colon cancer [10], breast cancer [13,14], or liver cancer cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that it has good anti-tumor effects [914]. For example, Tau can inhibit the in vitro invasion and migration of breast cancer cells and has a better therapeutic effect against methylbenzanthracene (DMBA)-induced breast cancer [11,12]. Our previous studies have shown that Tau can inhibit the apoptosis of cardiomyocytes subjected to ischemia/reperfusion [15] and can induce (or promote) apoptosis in colon cancer [10], breast cancer [13,14], or liver cancer cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…An inequality between the antioxidants and ROS occurs oxidative stress due to the formation of reactive oxygen is larger than the cells’ capability to detoxify the reactive intermediates, which show the way to oxidative injury to molecules . The production of antioxidants is a most important mechanism for defending cells against a diversity of exogenous and endogenous toxic chemicals of DMBA and ROS . In the current work, the decreased activities of these antioxidant enzymes were found in cancer induced rats and this could be owing to these enzymes are not enough to scavenging of ROS .…”
Section: Discussionmentioning
confidence: 54%
“…Experimental animals were divided into four groups of six rats each as follows. Group I: Normal control animals fed with standard diet and pure drinking water. Group II: Animals treated with a single dose of DMBA (25 mg /kg b.wt) in 1.0 mL olive oil by gastric intubation to induce breast cancer. Group III: Breast cancer bearing animals were post‐treated with Taurine (100 mg/kg b.wt in pure drinking water by gastric intubation) after the 10th week of DMBA administration and continued up to 15th week . Group IV: Control animals treated with taurine alone (as in group III). …”
Section: Methodsmentioning
confidence: 99%